THE STRIVING TO STAY ALIVE REFLECTED IN JONATHAN SWIFT GULLIVER'S TRAVELS (1926) : AN INDIVIDUAL PSHYCHOLOGICAL APPROACH - Hartomy, Andre (2011)
The study is reveal how the strive for achieving happiness of the major character influences his personality. The objective of the study is to analyze the novel based on the structural analysis and the individual psychological analysis. This study is qualitative study. The object of the study is Gulliver's Travels published in 1926 in England.The primary data source is the novel itself and the secondary data source is the other sources related to the analysis such as the author‟s biography, essay, and other literary work, which are related to this study . the method of data collection is library research. The technique of data analysis is descriptive analysis. The study comes to the following conclusion, first based on the structural analysis of each elements, it show that the character and characterization, plot, point of view, setting of place and time and the other elements have the unity and successfully relate to one another then finally formulated into good quality of a novel, second , based on the Individual analysis, it is evident that in this novel, Gulliver has some efforts to reach his happiness with his wife and child and he can travel in all over world, it can be seen from his effort to make his dream come true